Male-specific fruitless isoforms target neurodevelopmental genes to specify a sexually dimorphic nervous system. - Neville, M.C.; Nojima, T.; Ashley, E.; Parker, D.J.; Walker, J.; Southall, T.; Van de Sande, B.; Marques, A.C.; Fischer, B.; Brand, A.H.; Russell, S.; Ritchie, M.G.; et al. (Current Biology, 2014)
In Drosophila, male courtship behavior is regulated in large part by the gene fruitless (fru). fru encodes a set of putative transcription factors that promote male sexual behavior by controlling the development of sexually dimorphic neuronal circuitry. Little is known about how Fru proteins function at the level of transcriptional regulation or the role that isoform diversity plays in the formation of a male-specific nervous system.To characterize the roles of sex-specific Fru isoforms in specifying male behavior, we generated novel isoform-specific mutants and used a genomic approach to identify direct Fru isoform targets during development. We demonstrate that all Fru isoforms directly target genes involved in the development of the nervous system, with individual isoforms exhibiting unique binding specificities. We observe that fru behavioral phenotypes are specified by either a single isoform or a combination of isoforms. Finally, we illustrate the utility of these data for the identification of novel sexually dimorphic genomic enhancers and novel downstream regulators of male sexual behavior.These findings suggest that Fru isoform diversity facilitates both redundancy and specificity in gene expression, and that the regulation of neuronal developmental genes may be the most ancient and conserved role of fru in the specification of a male-specific nervous system.